2016
DOI: 10.1039/c6cc04381j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of tertiary arylamines: Lewis acid-catalyzed direct reductive N-alkylation of secondary amines with ketones through an alternative pathway

Abstract: We report herein a highly efficient, tin(ii)/PMHS catalyzed reductive N-alkylation of arylamines with ketones affording tertiary arylamines. A very wide substrate scope was observed for the current catalytic method as all six permutations of ketones/aldehydes/heterocyclic carbonyls and primary/secondary/heterocyclic amines were well tolerated, enabling access to secondary, tertiary and heterocyclic amines. The method is also convenient for the synthesis of N-substituted isoindolinones and phthalazinones via a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Some screening outcomes are compiled in Table . Initially, the reaction between a and b was carried under previously developed conditions and surprisingly, reaction resulted in excellent yield of desired amine (Table , entry 1). Further, relatively lower yield of the amine was obtained with less catalyst loading (Table , entry 2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Some screening outcomes are compiled in Table . Initially, the reaction between a and b was carried under previously developed conditions and surprisingly, reaction resulted in excellent yield of desired amine (Table , entry 1). Further, relatively lower yield of the amine was obtained with less catalyst loading (Table , entry 2).…”
Section: Resultsmentioning
confidence: 99%
“…To overcome the challenges associated to developed protocols, our group have developed new catalytic approaches for the synthesis of tertiary amines using various alkylating agents such as carbonyls and alkynes via an alternative carbocationic pathway . During our previous study on the direct reductive N‐alkylation of secondary anilines with carbonyl compounds, we found that initially, the carbonyl compound is reduced to alcohol intermediate.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations